Bottom-up synthesis of molecular nanodiamond from nanographene - Jiaxu Liang; Christopher P. Ender; Nancy C. Forero-Martinez; Ilyes Batatia; Jingyi Liu; Xin Yang; Raul Gonzalez Brouwer; Lev Kazak; Rémi Blinder; Leonardo Cancellara; Nadezda V. Tarakina; Yizhi Liu; et al. (Nature, 2026)
Abstract Nanodiamonds hosting colour centres are promising building blocks for quantum technologies, enabling advances in quantum computation 1,2 , nanoscale NMR spectroscopy 3–6 , single-spin magnetometry 7,8 , wide-field quantum imaging 9 and single-photon sources 10,11 . However, the controlled bottom-up synthesis of ultrasmall and structurally uniform nanodiamonds has remained a challenge, with existing methods producing heterogeneous materials that vary in size, morphology, impurity content and defect quality. Here we show that well-defined, hydrogen-terminated molecular nanographenes serve as chemically confined precursors for high-pressure, high-temperature synthesis of ultrasmall (3–4 nm), monodisperse and highly crystalline molecular nanodiamonds with only a single sp 2 surface reconstruction and produced on a milligram scale. The same bottom-up platform also enables a two-component strategy for incorporating silicon- and germanium-based colour centres during synthesis, yielding SiV − and GeV − emitters without ion implantation, irradiation or post-treatment. Because the nanographene precursor defines both the confined carbon framework and the hydrogen content, this approach provides intrinsic, precursor-level control over nanodiamond size and composition, particularly in the low-nanometre regime relevant for biological and quantum sensing. Molecular nanographenes, ultralarge polycyclic aromatic hydrocarbons, therefore, establish a scalable and modular route to high-quality molecular and fluorescent nanodiamonds and offer a general design principle for tailored quantum materials and nanoscale devices.